E-box binding transcription factors in cancer - Pan, Yuanzhong; van der Watt, Pauline J.; Kay, Steve A. (Frontiers in Oncology, 2023)
E-boxes are important regulatory elements in the eukaryotic genome. Transcription factors can bind to Eboxes through their basic helix-loop-helix or zinc finger domain to regulate gene transcription. E-boxbinding transcription factors (EBTFs) are important regulators of development and essential for physiological activities of the cell. The fundamental role of EBTFs in cancer has been highlighted by studies on the canonical oncogene MYC, yet many EBTFs exhibit common features, implying the existence of shared molecular principles of how they are involved in tumorigenesis. A comprehensive analysis of TFs that share the basic function of binding to E-boxes has been lacking. Here, we review the structure of EBTFs, their common features in regulating transcription, their physiological functions, and their mutual regulation. We also discuss their converging functions in cancer biology, their potential to be targeted as a regulatory network, and recent progress in drug development targeting these factors in cancer therapy.